IMPACT OF HYDROALCOHOLIC CONCENTRATE OF HEMIDESMUS INDICUS AGAINST 1-METHYL-4-PHENYL-1,2,3,6-TETRAHYDROPYRIDINE PROMPTED PARKINSONISM IN MICE - V, CHITRA; K, MANASA; SHARON S, EVELYN; CHOUDHURY, SHATABDI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to evaluate the protective effect of Hemidesmus indicus against 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced mice model. Methods: A total of 18 male Swiss Albino mice were divided into three groups (n=6). Hydroalcoholic concentrate of H. indicus (HAHI) at 200 and 400 mg/kg dosages, 30 min before the MPTP (20 mg/kg, intraperitoneal organization) treatment, was regulated for 7 days, and behavioral assessment was made by rotarod test, grip strength test, locomotor activity, and catatonia behavioral study. Appraisal of cell reinforcement catalysts, such as thiobarbituric acid reactive substance (TBARS), superoxide dismutase, catalepsy, glutathione (GSH) peroxidase, and GSH, were also assessed to screen the neurotoxicity incited by MPTP. Results: In the present investigation, the neuroprotective impacts of the hydroalcoholic concentrate of H. indicus were assessed, Which is known for its monoamine oxidiase activity, stimulant, anti-convulsant activity and a section of it is used as nerve tonic Frozen at 8 degree C. The cell viability analysis and IC50 determination in SH-SY5Y neuroblastoma cell lines were performed by MTT assay, and neuronal red uptake assay and HAHI were found to have a significant IC50 value in SH-SY5Y cells. Conclusion: The outcomes demonstrated that HAHI essentially enhanced the behavioral studies, striatal neurotransmitter content, and antioxidant status in a dose-dependent manner lessened TBARS level.